ROVE BEETLES (COLEOPTERA, STAPHYLINIDAE) AND THEIR MEDICAL IMPORTANCE - B. Janbakhsh; A. Ardalan (Tehran University of Medical Sciences, 1977)
Rove beetle dermatitis produced by the family Staphylinidae genus Paederus has world- wide distribution some one hundred species of Paederus have been found, but it is believed that only 30 of these produce dermatitis. Up to 1976 three species of paederus have been found in Iran as: P. fusciped Curtis; P. pietschmanni Bershaner , and P. spectabilis Kraatz . Observations on the biology of Paederus SPP have shown that the greatest activity coincides with a high degree of humidity during the hot season. Some species seem to be attracted to artificial light. The most common pathological feature caused by rose beetles is a viscular dermatitis Eye lesions may occur, but they are the result of spread of the irritant with the fingers, after the insect was crushed on the skin, therefore secondary infection. Experiments have shown that dermatitis only develops when a rove beetle is crushed on the haemolymph. The vesicant substance is pederin which is distinct from cantharidin in terns of its biological, physical, and chemical propertics.